The Effect of Banking Digitalization Through Self-Service Technology on Satisfaction and Loyalty of Customers Users of Sharia Bank Digital Services - Zaid Raya Argantara; Ahmad Choiri (Fakultas Ekonomi dan Bisnis Islam, 2023)
Several sectors, including the financial industry, have widely used today's technology. This is marked by the emergence of financial technology (fitech). One of Fitech in banking is self-service technology. This study aimed to determine the effect of banking digitization through self-service technology on customer satisfaction and loyalty who use Islamic banking digital services at BPRS Bhakti Sumekar. This research is quantitative research with a correlational research type. The sample in this study was 100 internet banking users at BPRS Bhakti Sumekar Sharia Bank, who were taken using a simple random sampling technique. Data collection was carried out using questionnaires, observation, and documentation. The researchers analyzed the data quantitatively with the help of SPSS. The study results show a positive effect of banking digitization through self-service technology on customer satisfaction using Islamic bank digital services at BPRS Bhakti Sumekar. The influence of banking digitization through self-service technology on customer satisfaction using Islamic bank digital services at BPRS Bhakti Sumekar is 64.7%.